The MIR-NAT MAPT-AS1 does not regulate Tau expression in human neurons - Rafaela Policarpo; Leen Wolfs; Saul Martínez-Montero; Lina Vandermeulen; Ines Royaux; Gert Van Peer; Pieter Mestdagh; Bart De Strooper; Annerieke Sierksma; Constantin d’Ydewalle (PLoS ONE, 2025)
The MAPT gene encodes Tau protein, a member of the large family of microtubule-associated proteins. Tau forms large insoluble aggregates that are toxic to neurons in several neurological disorders, and neurofibrillary Tau tangles represent a key pathological hallmark of Alzheimer’s disease (AD) and other tauopathies. Lowering Tau expression levels constitutes a potential treatment for AD but the mechanisms that regulate Tau expression at the transcriptional or translational level are not well understood. Natural antisense transcripts (NATs) are a particular class of long non-coding RNAs (lncRNAs) that can regulate expression of their overlapping protein-coding genes at the epigenetic, transcriptional, or translational level. We and others identified a long non-coding RNA associated with the MAPT gene, named MAPT antisense 1 (MAPT-AS1). We confirmed that MAPT-AS1 is expressed in neurons in human post mortem brain tissue. To study the role of MAPT-AS1 on MAPT expression regulation, we modulated the expression of this lncRNA in human neuroblastoma cell lines and in human induced pluripotent stem cell (iPSC) derived neurons. In contrast to previous reports, we observed no changes on MAPT mRNA or Tau protein levels upon modulation of MAPT-AS1 levels in these cellular models. Our data suggest that MAPT-AS1 does not regulate Tau expression levels in human neurons in vitro. Thus, MAPT-AS1 does not represent a valuable therapeutic target to lower Tau expression in patients affected by tauopathies including AD.